Bamatel handicraft store artesanias “Bamatel” - Ponce Burgos, Karen Katiana
Artesanías Bamatel” is carried out in the municipality of San Sebastián, department of San Vicente, El Salvador; this small town is known for making hammocks, tablecloths and bedspreads, that is why this place becomes the ideal and strategic location to attract our market objective. As it is known, tourism is very important from the social, cultural and economic point of view. Thanks to tourism, investment in infrastructure and buildings increases significantly, generates a higher level of development in the areas involved, as well as increasing foreign exchange. Unemployment rates are falling sharply because of tourism, generating greater well-being in the affected communities. Our main goal is to offer our customers a wide range of artisan products that are functional and economical, designed with materials of the best quality. In this way, we intend to contribute to the development of our people, generating employment and income that will help the economy of San Sebastián. Tourism in our village is mainly because of all the artisanal products that different businesses offer to tourists, we stand out also by offering products at an affordable price, since these products are made in our town allows us to offer a fair price to our customers.